Implementation of Industrial Narrow Band Communication System into SDR Concept - Bobula, Marek; Danek, Karel; Prokes, Ales (Společnost pro radioelektronické inženýrství, 2008)
The rapid expansion of the digital signal processing has penetrated recently into a sphere of high performance industrial narrow band communication systems which had been for long years dominated by the traditional analog circuit design. Although it brings new potential to even increase the efficiency of the radio channel usage it also forces new challenges and compromises radio designers have to face. In this article we describe the design of the IF sampling industrial narrowband radio receiver, optimize a digital receiver structure implemented in a single FPGA circuit and study the performance of such radio receiver architecture. As an evaluation criterion the communication efficiency in form of maximum usable receiver sensitivity, co-channel rejection, adjacent channel selectivity and radio blocking measurement have been selected.
Keywords: Radio receivers; radio telemetry; communication system performance; digital radio; software defined digital radio